SEARCH ENGINE update - Notess, Greg R (Online searcher (Medford, N.J.), 2017)
DuckDuckGo has expanded the computer language coverage in its Instant Answers with more content available for C, C#, C++, CSS, Haskell, HTML, Java, JavaScript, Objective-C, Perl, PHP, Python, R, Ruby, Scala, and Swift. Google has added information from the U.S. Department of Education College Scorecard for college searches, displaying this information as quick answers for topics covered in the Scorecard, such as graduation rate, average total cost with aid, average salary after attending that institution, acceptance rate, and undergraduate tuition and fees.